PENGEMBANGAN MODUL IPA TERPADU SAINTIFIK LEARNING TERHADAP PENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS VII MTS SABILURROSYAD BARABALI - MULIA RASYIDI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The objectives of this study were: 1) the characteristics of the science-based learning module on the interaction between living things and the environment; 2) the feasibility of the science-based learning module on the material of the interaction of living things with the environment that has been developed in science learning; 3) the effectiveness of the science-based learning module on the interaction between living things and the environment. The research carried out is research and development (R&D). The development model implemented is the Four-D model adapted from Thiagarajan (1974) which consists of four stages including: define, design, develop, and disseminate. The subject of a limited trial was carried out on 9 students of class VII F at MTs Sabilurrosyad Barabali and a wide-scale trial was implemented for 30 students in class VII D at MTs Sabilurrosyad Barabali. The trial use used pre-experimental design type One-Shot Case Study. The analysis technique implemented is descriptive qualitative-quantitative. The results of the research show that: 1) the characteristics of the science-based learning module to improve critical thinking skills and learning outcomes on the interaction between living things and the environment have been successfully developed using the Four-D development model, 2) the module eligibility results are validated by expert validators, education practitioners, peers, and the responses given by educators and students after learning using modules, the results are that the modules are categorized as very good and feasible to be implemented in learning, 3) The effectiveness of the modules can be seen from a high level of readability and according to ability or mastery. Students’ understanding of the module being developed, in this study, what was tested was the effectiveness of the module on critical thinking skills and student learning outcomes. The effectiveness of the module can be seen from the average percentage of students’ high critical thinking skills in each learning activity, namely KB I 76, 97% in sufficient categories, KB II has increased 85.72% in good categories, and in KB III increased 89, 32% with good category. The average learning outcomes of students in the knowledge aspect of KB I-KBIII increased, with details in KB I 85% of students have reached KKM, KB II 83.34% of students have reached KKM, KB III 96.64% of students have reached KKM. the average student learning outcomes in the attitude aspect increased from KB I to KB III to 3.25 consecutively; 3.36; 3.47 with good criteria. The average skills aspect of the students’ learning outcomes increased from KB I - KB III to 3.07; 3.30; 3.45 with good criteria. It can be concluded that the integrated science learning module is effective for improving critical thinking skills and student learning outcomes.